2014
DOI: 10.1242/jeb.107474
|View full text |Cite
|
Sign up to set email alerts
|

The elaborate plumage in peacocks is not such a drag

Abstract: One of the classic examples of an exaggerated sexually selected trait is the elaborate plumage that forms the train in male peafowl Pavo cristatus (peacock). Such ornaments are thought to reduce locomotor performance as a result of their weight and aerodynamic drag, but this cost is unknown. Here, the effect that the train has on take-off flight in peacocks was quantified as the sum of the rates of change of the potential and kinetic energies of the body (P CoM ) in birds with trains and following the train's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Recently, Askew19 found that the train did not reduce take off flight performance, which combined with our results, indicates that neither terrestrial or volant locomotion are negatively impacted by the exaggerated sexually selected train of peacocks. The maintenance of economical locomotion during periods when locomotor behaviour is focused on procuring a mate is likely to be particularly important for reducing the overall costs13.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Recently, Askew19 found that the train did not reduce take off flight performance, which combined with our results, indicates that neither terrestrial or volant locomotion are negatively impacted by the exaggerated sexually selected train of peacocks. The maintenance of economical locomotion during periods when locomotor behaviour is focused on procuring a mate is likely to be particularly important for reducing the overall costs13.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have made inferences about the costs of carrying exaggerated traits by either removing or artificially exaggerating them further51516171819. However, while manipulating sexually selected traits by artificially removing them will produce clearly defined experimental testing of the role of the train it does mean any changes in general body condition, hormone levels, plumage quality or the influence of diurnal rhythms is not taken into account in the animals being investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent work on peacocks, hummingbirds, and rhinoceros beetles ( Trypoxylus dichotomus ) found that longer, and theoretically more unwieldy, tails/horns do not negatively impact various aspects of flight (Clark and Dudley ; McCullough et al. ; Askew ), potentially dismissing this idea. Instead, the evolved pairing between display flashiness and plumage patch size among species may have arisen because a bigger area of feathers may be more difficult to coordinate and orient to produce uniform/specific flash patterns.…”
Section: Discussionmentioning
confidence: 99%